Experimental results of microcontroller based FC-TSR-TCR systems / T. Vijayakumar and Dr. A. Nirmalkumar - Vijayakumar, T.; Nirmalkumar, A. (Dr.) (UiTM Press, 2010)
This paper deals with the simulation and experimental results of Fixed Capacitor Thyristor switched Reactor Thyristor controlled reactor (FC-TSR-TCR) system. The FC-TSRTCR system is simulated using MATLAB and the simulation results are presented. The power and control circuits are simulated. Laboratory model for the FC-TSR-TCR system is implemented using Atmel microcontroller and it is tested. The current drawn by the FC-TSR-TCR varies with the variation in the firing angle. Stepped variation of current is obtained using thyristor switched reactor. The experimental results are compared with the simulation results.